Die wirtschafts- und sozialgeographische Struktur iranischer Dörfer nach der Bodenreform - Hahn, Helmut (ERDKUNDE, 1973)
The structural analysis of a number of selected Iranian villages should enable a) a comparison with the results of earlier research in villages in the nearly Afghanistan, and b) should help to show changes in the social and economic situation since the land reform, and c) should show up the effectiveness of the governmental development policy. On the whole, definate improvements in the standard of living of the rural population, an intensification of land-use and progress in the methods of cultivation can be recognized as a result of high capital and personnel investment. Problematic are the break-up of newly established small holdings through divided inheritance and the yet insufficient cooperation of the farmers, whom the government induces to do big experiments on a cooperative basis.